Pengaruh Corporate Social Responsibility dan Green Accounting Terhadap Kualitas Laba dengan Type of Industry sebagai Variabel Moderasi - Febriyanti, Eny; Rosini, Iin; Nofryanti, Nofryanti (Universitas Batanghari Jambi, 2024)
The aim of this research is to examine, across all industries listed on the BEI in 2019-2021, the influence of CSR and environmentally friendly accounting on earnings quality, by controlling for the influence of industry type. Quantitative methods were used in this research. This research uses data from 65 companies traded on the Indonesia Stock Exchange between 2019-2021 as the sample. Panel data regression analysis is used to analyze the data. This research finds that there is a negative relationship between corporate social responsibility and earnings quality, and there is a similar negative relationship between environmentally friendly accounting and earnings quality. There is no relationship between corporate social responsibility (CSR) and industry type, and there is no relationship between industry type and green accounting.